Characterization of site conditions in Greece for realistic seismic ground motion simulations: Pilot application in urban areas - Kiratzi, A.; Klimis, N.; Theodoulidis, N.; Margaris, V.; Makra, K.; Christaras, B.; Chatzipetros, A.; Papathanassiou, G.; Savvaidis, A.; Pavlides, Sp.; Roumelioti, Z.; Sapountzi, L.; et al. (Bulletin of the Geological Society of Greece, 2013)
We present the structure and first results of the "Thales" project on site classification in Greece. The aim of the project is twofold: to develop and present a methodology for the characterization and classification of site conditions based on their geological, geomorphological and geophysical characteristics and to apply the proposed methodology to case studies in Greece, including the urban areas of Xanthi, Edessa and Grevena. In particular, the units described on a surficial geological map will be correlated to shear-wave velocity data, corresponding to the upper 30m (Vs30) of the soil column, aiming to produce first order maps to help practitioners and provide the tools to realistically predict ground motions triggered by an earthquake. The classification will be based on information provided by borehole logs, where velocity profiles were measured and will be validated using the three case studies. The outcome of the project will be usable by national agencies and decision makers for urban planning.